Pedagogical strategies of Islamic architecture within higher education: paper review - Hasnan, Liyana; Utaberta, Nangkula; Ismail, Sumarni (IIUM Press, 2020)
The teaching/learning environment is constantly changing; however, traditional lecture-based pedagogy has remained fundamentally unchanged. This is particularly true with the teaching of History of Architecture where trends of contents and teaching have not changed. Passive learning of knowledge could lead learners to experience cultural alienation and be disassociated from contemporary issues. The research asserts that Islamic architecture is a discourse occupied with complexities and ruptures, and educational strategies can address these multiple realities of constructions. The research finds that the discourse of Islamic architecture is a complex subject with multiple narratives that are often swept under a metanarrative, positioned as the ‘other’ towards Western history. The paper intends to identify multiple histories and narratives within Islamic architecture, and the paper posits that developing the course syllabus can help facilitate critical learning. The research applies the qualitative methodology of a systematic literature review. A new approach to archival content can have encouraging effects on how the discourse is understood and made relevant to contemporary issues. Contents of diverse context and issues facilitate critical learning, enabling students to construct an encompassing understanding of Islamic architecture.